A financial cost-benefit analysis of the implementation of a small-camp system in ostrich farming to allow veld restoration - Mugido, Worship (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScAgric (Agricultural Economics))--University of Stellenbosch, 2011.